Maxillo-facial reconstruction following cancer ablation during COVID-19 pandemic in southern Italy. (April 2021) - Rauso, Raffaele; Chirico, Fabrizio; Federico, Francesco; Francesco Nicoletti, Giovanni; Colella, Giuseppe; Fragola, Romolo; Pafundi, Pia Clara; Tartaro, Gianpaolo
Highlights: In COVID-19 era, the aim of our effort is to guarantee high-quality and timely oncologic care, minimizing infection risk. Microvascular flaps, reported to be the gold standard for reconstruction, require an extended resource allocation not affordable in this period. We are obliged to define a paradigm shift in our approach, based on propeller flap. This surgical technique could represent a reconstructive landmark in COVID-19 era, besides head and neck reconstructive surgery is most likely heading towards a new reconstructive approach. Abstract: In COVID-19 pandemic era, one major concern is related to ensure optimal management to oncologic patients, even though a context of radical uncertainty. The aim of our effort is to guarantee high-quality and timely care, minimizing COVID-19 infection risk, according to our head and neck (HN) reconstructive mission, still more challenging because of the criticality of the period. Thus, our reconstructive decision algorithm is changed. Microvascular free flaps, reported to be the gold standard for surgical reconstruction, represent extremely specialized procedures necessitating an extended resource allocation not affordable in the adversities of the period. Therefore, we are obliged to define a paradigm shift in our approach, based on free-style reconstructive surgery principles of propeller flap concept. According to our experience, we believe that this viable and feasible surgical technique could represent a reconstructive landmark in this pandemic era, since any guideline is missing, besides HN reconstructive surgery is most likely heading towards a new reconstructive approach.